Prediction and investigation of surface quality in high speed end-milling of silicon to eliminate conventional finishing operations - Amin, A. K. M. Nurul; Ismail, Mohd Dali M; Musa, Muhammad Iqbal; Patwari, Anayet Ullah (Trans Tech Publications, Switzerland, 2012)
Surface finish and dimensional accuracy are two of the most important requirements in machining process. High speed machining (HSM) is capable of producing parts that require little or no grinding/lapping operations within the required machining tolerances. In HSM determination of the optimum combination of cutting parameters for achieving the required level of quality, such as, minimum possible surface roughness and maximum tool life is a very important task. Silicon is conventionally finished using grinding followed by polishing and lapping to achieve required surface finish and surface integrity. In this study small diameter tools are used to achieve high rpm to facilitate the application of low values of feed and depths of cut to ensure high surface roughness values through achievement of ductile mode machining of silicon. Investigations on the effect cutting parameters of high speed end milling on surface finish and integrity of silicon has been conducted to minimizing the amount of finishing requirement in machining of silicon, with the objective of reducing cost and increasing effectiveness of silicon manufacturing process. In this work statistical models were developed using the capabilities of Response Surface Methodology (RSM) to predict the surface roughness in high speed flat end milling of silicon under dry cutting conditions.